Transforming Mangrove Monitoring into Digital Climate Learning: A Spatiotemporal Insight from Bengkulu City, Indonesia - Srifitriani, Abditama; Soeprobowati, Tri Retnaningsih; Puryono, Sri (Corolla International Conference, 2025)
This study investigates how mangrove monitoring can be converted into a digital learning resource to enhance climate literacy. Focusing on Bengkulu City, Indonesia, the research combines remote sensing analysis with digital pedagogy to provide a spatiotemporal view of changes in the mangrove ecosystem. Multi-temporal satellite data from 1995, 2005, 2015, and 2025 were analyzed using Random Forest classification to identify patterns of mangrove loss, stability, and regrowth. The findings indicate a 57.3% decline in mangrove vegetation cover from 1995 to 2025, with some recovery observed after 2015 due to local restoration efforts. By integrating GIS, the spatial data was transformed into an interactive digital module that allows learners and community members to explore climate-related changes more intuitively. Evaluation of the module revealed an average learning improvement of 25%, particularly in spatial reasoning and understanding of climate-ecosystem relationships. The results demonstrate that converting ecological data into digital educational media can connect scientific knowledge with public awareness, positioning mangrove monitoring as both a conservation initiative and a tool for climate-resilient education.